7(-4m-6)=8m+6(2-3m)

Simple and best practice solution for 7(-4m-6)=8m+6(2-3m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(-4m-6)=8m+6(2-3m) equation:


Simplifying
7(-4m + -6) = 8m + 6(2 + -3m)

Reorder the terms:
7(-6 + -4m) = 8m + 6(2 + -3m)
(-6 * 7 + -4m * 7) = 8m + 6(2 + -3m)
(-42 + -28m) = 8m + 6(2 + -3m)
-42 + -28m = 8m + (2 * 6 + -3m * 6)
-42 + -28m = 8m + (12 + -18m)

Reorder the terms:
-42 + -28m = 12 + 8m + -18m

Combine like terms: 8m + -18m = -10m
-42 + -28m = 12 + -10m

Solving
-42 + -28m = 12 + -10m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '10m' to each side of the equation.
-42 + -28m + 10m = 12 + -10m + 10m

Combine like terms: -28m + 10m = -18m
-42 + -18m = 12 + -10m + 10m

Combine like terms: -10m + 10m = 0
-42 + -18m = 12 + 0
-42 + -18m = 12

Add '42' to each side of the equation.
-42 + 42 + -18m = 12 + 42

Combine like terms: -42 + 42 = 0
0 + -18m = 12 + 42
-18m = 12 + 42

Combine like terms: 12 + 42 = 54
-18m = 54

Divide each side by '-18'.
m = -3

Simplifying
m = -3

See similar equations:

| -19.1=x-1.9+x | | .5(s+9)=39 | | 42x^9-147x^7=0 | | 5b=-15+8b | | 6-(4y+1)=5(y+1)-y | | 6(t-1)=9(r-4) | | 1.6(d+-2)=40 | | y^2-3x-6y=8 | | 15y^2+29y+12= | | 49-54= | | 9x+2(x-1)=11x+8 | | 3(2x-1)+x=-x-3 | | 8k+k-7-10k= | | 3(2x+4)+6=2(x-5) | | 42m=999 | | 4-3x=26 | | 3x^2+17x+8= | | 42m=9999 | | 1000000+100000000000000000000000000000= | | 3(2x+4)+6=2x-5 | | 180=16r^2 | | 15=-9+x | | 9r^3-36r=0 | | =350-14x | | 20=-5y-3x | | -154x=6-3x | | Y-4y=-60 | | -x=5x-12 | | -24x+9=-3x-4 | | 5x-7x-3=8 | | f(x)=4xsquared-13x+3 | | 3.5-.60+8.3-4.2=t |

Equations solver categories